(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2009)
Verbal behavior is operant behavior and, therefore, is ruled by the laws of reinforcement. Reinforcement contingencies may result in suppression or low frequency of verbal responses. The purpose of this study was threefold: To formulate hypotheses of possible reinforcement contingencies that might suppress or lower the frequency of verbal responses; to observe family interactions and identify the contingencies that could lower the frequency of verbal responses and raise the frequency of inappropriate behavior; to develop intervention procedures through parent counseling and to verify possible changes in the frequency of verbal responses emitted by a 5 yearold child. In order to accomplish this aim, an interview was conducted to assess the history of the childs and the parents complaints; one hour observation sessions in the childs home were held over 7 months and, at the end of each observation session, parent counseling took place. The purpose of counseling the parents was to instruct them to differentially reinforce alternative responses, teach naming, reinforce vocal mands, prompt the emission of verbal responses, alter the frequency of watching TV and playing video games, and perform the extinction of inappropriate behavior. The interactions of family members during the intervention sessions were noted and categorized. The results show that the child was exposed to unfavorable contingencies at the beginning of the experiment and in his earlier life, which had given rise to the suppression and/or low frequency of verbal responses. The instructions given by the researcher seem to have produced changes in the parents behavior and, consequently, in the childs behavior, leading to an increased frequency of verbal responses and a decreased frequency of inappropriate behavior. In addition, the data show that changes occurred in the interactions of all members of the family, confirming that verbal behavior is shaped and maintained by reinforcement contingencies.